The Influence of Bid-Ask Spread, Market Value, Variance Return, and Stock Trading Volume on the Stock Holding Period on the SRI-KEHATI Index listed on the Indonesia Stock Exchange in 2018-2022 - Paramita, Santi; Nursyamsi, Yusriyah Amelia (International Journal of Finance Research, 2023)
The increasing awareness of society to play a role in preserving the environment has encouraged more and more investors to choose environmentally friendly stocks. One of the environmentally friendly stock indexes in Indonesia is the SRI-KEHATI Index. This research aims to determine the factors that influence the holding period of SRI-KEHATI Index stocks. Thus, this research examines the influence of bid-ask spread, market value, return variance, and stock trading volume on the stock holding period. The research focuses on the SRI-KEHATI Index listed on the Indonesia Stock Exchange in 2018-2022. The research uses quantitative methods with descriptive and associative approaches. The population in this study was 41 companies. Sampling used a purposive sampling technique with a total sample of 13 companies so 65 observation data were obtained. The data analysis technique uses panel data regression analysis. Partial test results show that the bid-ask spread and return variance do not affect the stock holding period. Market value and stock trading volume positively affect the stock holding period. Simultaneous testing shows that bid-ask-spread, market value, return variance, and stock trading volume impact the stock holding period.